Communication-related concerns of family caregivers of older adults living with dementia: A cross-sectional descriptive study - Komjakraphan, Patcharee; Karuncharernpanit, Sirikul; Kemsen, Sasithon; Kitphaiboonchai, Thanthip; Setthawatcharawaniche, Suwanna (Kasetsart Journal of Social Sciences, 2021)
The purpose of this study was to investigate the communication-related concerns of family caregivers of older adults living with dementia in Thailand. A cross-sectional study in which 115 caregivers from five outpatient clinics located in the central and southern regions of Thailand participated in a survey from May to October 2019. The survey questions spanned three topics: (1) communication problems and perceived communication difficulties; (2) communication strategies used and older adults’ positive responses and; (3) communication training support. Data collected were analyzed by using descriptive statistics with focus on frequency ranking and correlation. In general, most of the caregivers were females with daughter-mother or daughter-father relationships, and had taken on the role of main caregivers of the older adults from one to five years. The older adults’ ages ranged from 60– 94 years with a mean age of 76.3 years (SD = 7.8). The majority was female. TMSE scores ranged from 14–23 with the majority scoring 19 points (n = 78, 67.8%). The study results suggested that communication-related concerns among family caregivers of older adults living with dementia play a major role in their emotional burdens. Recognizing communication-related concerns should be utilized for designing an appropriate communication training program and implementing interventions for assisting family caregivers. A communication program assisting family caregivers to build a more open and positive relationships with older adults with dementia is recommended.